Presidential Partisanship in Indonesian Elections: A Legal and Ethical Analysis - Zuhdi, Achmad; Suparman, Eman; Perwira, Indra; Nguindip, Nana Charles (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
Presidential involvement in electoral contests in Indonesia has increasingly raised concerns regarding the neutrality and integrity of democratic processes. Instances such as the politicization of social assistance programs, the strategic appointment of acting governors, and the active participation of ministers in campaign activities have highlighted the pervasive use of state resources for partisan interests. This study examines the permissibility of presidential political partiality in electoral contests from legal and ethical perspectives. Employing a normative legal research method with a statute and analytical approach, the study analyzes primary legal sources, including the 1945 Constitution and relevant electoral regulations, as well as secondary scholarly materials. The findings reveal that presidential partisanship is legally and ethically unjustifiable. Legally, procedural mechanisms, such as the requirement for mandatory leave during campaign activities, fail to guarantee factual neutrality and enable covert partisanship. A systematic and teleological interpretation of Article 299 paragraph (1) of the Election Law demonstrates that the right to campaign applies exclusively to presidents running as candidates, not to incumbents who are not contesting. Ethically, presidential partiality violates principles of impartiality and moral legitimacy, undermining the president’s role as a unifying symbol of national integrity. The study emphasizes the urgent need for regulatory reforms and ethical standards to reinforce fairness and uphold public trust in Indonesia’s electoral process.